2018
DOI: 10.1242/jeb.181719
|View full text |Cite
|
Sign up to set email alerts
|

Haltere removal alters responses to gravity in standing flies

Abstract: Animals detect the force of gravity with multiple sensory organs, from subcutaneous receptors at body joints to specialized sensors like the vertebrate inner ear. The halteres of flies, specialized mechanoreceptive organs derived from hindwings, are known to detect body rotations during flight, and some groups of flies also oscillate their halteres while walking. The dynamics of halteres are such that they could act as gravity detectors for flies standing on substrates, but their utility during non-flight beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…In addition, in the fruitfly, three kinds of mechanosensory neurons have been found to code for the angular rate and the orientation of the leg joints 41 . Secondly, contrary to the prevailing belief that the halteres are involved in gravity perception 42 , 43 , the possible involvement of these organs to generate the goal roll signal was unlikely in this study, as no righting (but inverted flight) was observed in the condition where the fly triggered the wingbeat and thus the halteres’ vibration. Note that in this condition, in which the antennae were glued, the inverted flapping flight was stable, unlike the unstable flight observed in hawkmoths with clipped-off antennae 44 , 45 .…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, in the fruitfly, three kinds of mechanosensory neurons have been found to code for the angular rate and the orientation of the leg joints 41 . Secondly, contrary to the prevailing belief that the halteres are involved in gravity perception 42 , 43 , the possible involvement of these organs to generate the goal roll signal was unlikely in this study, as no righting (but inverted flight) was observed in the condition where the fly triggered the wingbeat and thus the halteres’ vibration. Note that in this condition, in which the antennae were glued, the inverted flapping flight was stable, unlike the unstable flight observed in hawkmoths with clipped-off antennae 44 , 45 .…”
Section: Discussioncontrasting
confidence: 82%
“…B 288: 20202375 same ways. We predicted that fruit flies, unlike blow flies, will still be able to perform fast takeoffs with halteres removed, because they have not been shown to rely on haltere input for non-flying behaviours [37]. Fruit fly takeoffs were conservatively defined as the first two wingbeats (based on spontaneous takeoff results; figure 1b).…”
Section: (D) Haltere Ablation Makes Calyptratae Takeoffs Less Stablementioning
confidence: 99%
“…Animals must transform forces acting on the head/body into commands to stabilize gaze/posture and orient, navigate, and regulate physiology ( Angelaki and Laurens, 2020 ; Chen et al, 2021 ; Daltorio and Fox, 2018 ; Yates et al, 2013 ; Yoder and Taube, 2014 ). Both sensory organs and bodies change as animals develop and age.…”
Section: Introductionmentioning
confidence: 99%